2013
DOI: 10.1155/2013/926060
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Thiazolidinedione and Evaluation of Its Modulatory Effect on IFN-γ, IL-6, IL-17A, and IL-22 Production in PBMCs from Rheumatoid Arthritis Patients

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease frequently characterized by chronic synovitis of multiple joints. The pathogenesis of RA is complex and involves many proinflammatory cytokines as Th17 related ones. PPARγ is a nuclear receptor activator that represses proinflammatory gene expression. Thus, this work aimed to synthetize a new thiazolidinedione (TZD) analogue based on a well-known anti-inflammatory and PPARγ agonist activity of this ring and evaluate its anti-inflammatory activity. After chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
(27 reference statements)
1
19
0
1
Order By: Relevance
“…For E-configuration, the chemical shifts of these olefinic protons should be around 6.52 ppm. The exclusive formation of Z-isomer in this condensation reaction has also been clearly demonstrated by X-ray analysis (Bruno et al, 2002) and reported in many other similar studies (Alegaon and Alagawadi, 2012;da Rocha Junior et al, 2013).…”
Section: Introductionsupporting
confidence: 75%
“…For E-configuration, the chemical shifts of these olefinic protons should be around 6.52 ppm. The exclusive formation of Z-isomer in this condensation reaction has also been clearly demonstrated by X-ray analysis (Bruno et al, 2002) and reported in many other similar studies (Alegaon and Alagawadi, 2012;da Rocha Junior et al, 2013).…”
Section: Introductionsupporting
confidence: 75%
“…Furthermore, SATB1 coordinates Th2 cell differentiation by positively regulating Gata3 (Notani et al, 2010). SATB1, NFIL3, MAF, and PPARG positively regulate the gene expression of the Th2 cytokine Il4 (Ribeiro de Almeida et al, 2009;Kashiwada et al, 2011;Lai et al, 2012;da Rocha Junior et al, 2013;Kwon et al, 2014). In addition to the positive effects on Th2 cell differentiation, NFIL3 suppresses Th17 cell development by directly binding and repressing the Rorg promoter .…”
Section: Th2 Cell-specific Tfs Are Positively Regulated By Stat6 and mentioning
confidence: 99%
“…In addition to the positive effects on Th2 cell differentiation, NFIL3 suppresses Th17 cell development by directly binding and repressing the Rorg promoter . PPARG is also known to suppress Th17 and Th1 cell differentiation by decreasing the level of IFNγ production in splenocytes (da Rocha Junior et al, 2013 (Wuelling et al, 2009) Fifteen TFs were associated with the differentiation of other Th cell subtypes without a reported main function in Th2 cell differentiation. Of these, eight (Ah,Stat3,Etv6,Hif1α,Irf7,Stat2,Batf,and Crem) were increased, and seven (Irf1, Irf8, Nfatc3, Pou2af1, Rora, Klf2, and Tcf7) were decreased by STAT6.…”
Section: Th2 Cell-specific Tfs Are Positively Regulated By Stat6 and mentioning
confidence: 99%
“…Some factors encourage the uncoupling of osteoblastic and osteoclastic activities, such as RANK/RANKL/OPG, but little is known about inflammatory factors involved in this process. In inflammatory rheumatic diseases, the situation is worsened by the production of inflammatory cytokines such as TNF-α, IL-17A, IL-6 and, more recently, IL-22 [11]. The present study aimed to investigate serum levels of cytokines and to correlate them with clinical and laboratory parameters of postmenopausal osteoporosis.…”
Section: Discussionmentioning
confidence: 98%